OUTCOME OF LAPAROSCOPIC PERCUTANEOUS EXTRA PERITONEAL CLOSURE VERSUS OPEN REPAIR FOR PAEDIATRIC INGUINAL HERNIA. A RANDOMIZED CONTROL TRIAL - Ahmed, Armaghan; Hashim, Imran; Mehmood, Farrakh; Haider, Naveed; Chattha, Aziz Ahmad; ayub, Ayesha (Journal of Ayub Medical College Abbottabad, 2022)
Background: Laparoscopic inguinal hernia repair (LIHR) has many benefits like less frequency of metachronous contralateral hernias, minimum complications, comparatively less duration of operation and better cosmetic outcome as compared to the open technique. Objective of the study was to compare the outcome of laparoscopic percutaneous extra-peritoneal closure (LPEC) and open repair for paediatric inguinal hernia in terms of contralateral metachronous hernia, operative time and recurrence. Methods: A randomized controlled trial was conducted at the Department of Paediatric Surgery, Children Hospital Lahore. Non-probability purposive sampling was used, and 296 cases were divided into group-1(managed with conventional open repair) and group-2 (managed with laparoscopic Percutaneous Extra-peritoneal closure). After taking informed consent, data was collected, and cases were studied for operative time, contralateral metachronous hernia and recurrence till 6 months postoperatively. Data analysis was done through SPSS 22.0. Chi-square and independent sample t-test was used for comparison. p-value ‰¤0.05 was taken as significant. Results: The mean operative time was statistically less in the LPEC group (24.79±3.44 minutes) when compared to the open repair group (28.71±4.54 minutes), p-value <0.001. In the Open repair group, there were 19 (12.8%) cases that had contralateral metachronous hernia, while in the LEPC group, 2 (1.4%) cases had contralateral metachronous hernia p-value <0.001. In the Open repair group, 4(2.7%) cases had a recurrence, while in LPEC group 1 (0.7%) cases had a recurrence, with statistically same recurrence rate, p-value >0.05. Conclusion: The LPEC technique is better than conventional open repair in terms of CMIH, operative time, and recurrence rate.